Association of Wrist Circumference and Waist-to-Height Ratio with Cardiometabolic Risk Factors among Type II Diabetics in a Ghanaian Population - Christian Obirikorang; Yaa Obirikorang; Emmanuel Acheampong; Enoch Odame Anto; Emmanuel Toboh; Evans Adu Asamoah; Bright Amakwaa; Emmanuella Nsenbah Batu; Peter Brenya (Journal of Diabetes Research)
The study determined the association of wrist circumference (WrC) and waist-to-height ratio (WHtR) with cardiometabolic risk factors among diabetics in a Ghanaian population. This cross-sectional study involved 384 diabetic patients at Begoro District Hospital, Ghana. Blood pressure, anthropometrics, and biochemical indices were measured. The overall prevalence of dyslipidaemia, metabolic syndrome (MetS), and hypertension was 42.4%, 76.3%, and 39.8%, respectively. The optimum cut-off range of WrC to identify individuals at increased cardiometabolic risk was 17.5 to –17.8 cm for men and 16.0 to 16.7 cm for women while that of WHtR was 0.52 to 0.61 for men and 0.53 to 0.59 for women. WrC for women was a significant independent predictor for MetS [aOR = 3.0 (1.39–6.72), p=0.005] and systolic blood pressure [aOR = 2.08 (1.17–3.68), p=0.012]. WHtR was a significant positive predictor for triglycerides [aOR = 3.23 (0.10–3.82), p=0.001] for women. Using Framingham risk scores, 61% of the subjects had elevated 10-year risk of developing cardiovascular diseases (CVDs), with no significant difference in gender prevalence. WrC [aOR = 6.13 (0.34–111.4), p=0.107] and WHtR [aOR = 2.52 (0.42–15.02), p=0.309] were associated with statistically insignificant increased odds of moderate-to-high risk of developing CVDs in 10 years. The use of gender-specific cut-offs for WrC and WHtR may offer putative markers for early identification of CRFs.